Fresh Moringa Stenopetala leaves consumption and its determinants among pregnant women in southern Ethiopia - Derbo, Zeritu Dewana; Debelew, Gurmesa Tura (Frontiers in Nutrition, 2024)
Background: A woman's health and nutritional status has significant impact on her pregnancy situation. However, many pregnant women are undernourished. Moringa stenopetala is a plant consumed worldwide in various forms, and its consumption showed a reduction in the incidence of malnutrition.Although Moringa stenopetala is rich in essential macro-and micronutrients, there is little evidence on the proportion and determinants of fresh Moringa stenopetala leaf intake among pregnant women. The objective of this study was to fill this gap in the littérature and provide a baseline evidence for further research or intervention by investigation the proportion and determinants of fresh Moringa stenopetala leaf intake among pregnant women in the Gamo zone, south Ethiopian region.A community-based cross-sectional study was conducted among 623 randomly selected pregnant women using a pre-tested and structured questionnaire via a face-to-face interview. The consumption pattern was assessed based on a self-reported dietary history over the last 30 days before data collection. Multivariable logistic regression model was fitted using STATA version 14. An adjusted odds ratio with a 95% confidence interval was reported to show an association between the dependent and independent variables with level of statistical significance at a p-value of <0.05.The proportion of fresh Moringa stenopetala leaves intake among pregnant women was 49.60% (95% CI: 45.67%, 53.52%). The déterminants of fresh moringa leaf intake were being below 24 years old